A novel adaptive FEC and bitrate control in home video transmission over wireless network. (8th October 2012) - Liao, I–Ju; Wu, Tin–Yu; Chu, Kuo–Chih; Lee, Wei–Tsong
Home media wireless network (HMWN) is getting more and more popular issue in the future world. Nowadays, most of video streaming algorithm use extra bandwidth to keep high–video quality. Furthermore, to guarantee quality of video streaming when error occur the retransmission and selection drops method should be present. We present a video stream algorithm in this paper that can make usage of bandwidth more efficient and also can be adaptive with error modules in wireless environment. The receiver decides a scheme in the end of frame and feedback to sender immediately before sender start encode next frame. For the home media and algorithm using, we put MPEG–4 to use which is the most popular video codec method in these days. A novel video stream algorithm was proposed in this paper that can make usage of bandwidth more efficient and also can be adaptive with error modules on HMWN.